COVID-19 and Its Effect on Tourism in Nepal - Kunwar , Nishan Raj; Bista, Nar Bahadur (Nepalese Journal of Economics, 2025)
This study examines the covid-19 and its effect on tourism in Nepal. Tourism development is the dependent variables. The selected independent variables are government travel restrictions, vaccination roll out, airline operation, economic instability, and global travel sentiments. The primary source of data is used to assess the opinions of respondents regarding government travel restrictions, vaccination roll out, airline operation, economic instability, global travel sentiments and tourism development. The study is based on primary data. The primary data were gathered from 200 respondents through questionnaires. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of covid 19 and its effect on tourism in Nepal The study showed that Government travel restriction is positively related to Tourism development. It indicates that Government travel restriction leads to Tourism development. Similarly, Vaccination rollout is positively related to Tourism development indicating that higher the level of Vaccination rollout, higher would be the Tourism development. Likewise, Airline operation has positive relationship with Tourism development. It shows that Airline operation leads to an increase in the Tourism development. Similarly, economic instability has positive relationship with tourism development. It reveals that economic instability leads to Tourism development. The result shows that there is positive relationship between Global travel economic instability and tourism development. It shows that an increase in the level of Global travel sentiment leads to the increase in the Tourism development.